High Accuracy Dual Probe Station for Near Field Scanning - Yuwono, Tito; Baharuddin, Mohd Hafiz (Buletin Ilmiah Sarjana Teknik Elektro, 2023)
Electromagnetic (EM) emissions are a major issue for electronic products. Besides electronic products being able to work according to their function, they must also comply with EMC standards to avoid producing excessive EM emissions. One technique for measuring EM emissions is near field measurements. This measurement technique can be used to determine the faulty components which contribute to the failure of complying to the EMC standards. A near field measurement system consists of near field probes, digital oscilloscope, and a probe station which can control the movement of the near field probe during measurement process. In this paper, the design and development of a dual probe near field measurement system or station with high accuracy will be discussed. From instrument testing, it can be concluded that the probe station can cover ample scanning area with movement accuracy up to 0.05 mm and it is able to work well according to the test scenario. The designed probe station is verified by measurement and highly recommended to be used for near field measurements.